61. GLUCOSE AND HBA1C INDICATORS OF DIABETIC PATIENTS AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Identify exchange of diabetic patient’s Glucose and HbA1c indicators through test values of three times.Subject and method: Retrospective study with sample size is 92 medical records’ diabetic patients. Data collected by data collection tableResults: The median values of Glucose after 3 consecutive tests were 147,5 mg/dL, 144,5 mg/ dL, 127 mg/dL. The median values of HbA1c after 3 consecutive tests were 7,6%, 7,6%, 7,4%Conclusion: Necessary to strengthen health education activities for diabetic patients.
Keywords: Glucose; HbA1c; diabetic type 2